Determinants of Firm Value with Environmental Performance as Moderating Variable - Tries Ariyani; Dwi Prastowo Darminto; Edy Supriadi (Budapest International Research and Critics University, 2022)
One of the impacts of technological developments is the emergence of online platforms that can change the process of communication and social interaction. The existence of these online platforms also has an impact on business development in Indonesia. Many startup companies in Indonesia are using social media as a digital marketing communication strategy to attract consumers and increase brand awareness. This research method is a literature review that analyzes journals related to Social Media Marketing, Internet Marketing, and digital marketing communication strategies. The results show that the creativity factor in content creation is very influential in increasing customer engagement through digital marketing carried out by startup companies.